Towards resilient civilian-military interfaces on the coasts: addressing social vulnerability drivers - A Bukvic; T Cooper; B Richardson; L Delgado (Environmental Research: Climate)
Coastal flooding poses a significant threat to communities, infrastructure, and ecosystems across the United States and is exacerbated by sea level rise. It also places coastal assets vital for national security at risk, such as military installations and supporting civilian and private sectors. Substantial research and policy are focused on community adaptation and resilience. However, less attention has been given to coastal places with complex and unique characteristics shaped by their proximity to and dependence on military installations. Thus, the main objective of this study is to assess selected social vulnerability around nine military installations at high risk of coastal flooding along the US East and Gulf Coasts and determine if they have distinctive vulnerability patterns with implications for coastal resilience. The representative coastal military installations were selected from the Department of Defense Regional Sea Level Database based on their coastal flood risk and verified by the Federal Emergency Management Agency’s National Risk Index data. The social vulnerability indicators were determined within a 5 mile buffer around selected installations using geospatial analysis. The results indicate significant differences in social vulnerability across coastal installations of interest, with minority populations, housing cost burden, poverty, and underage populations being the most prevalent in all locations. The study underscores the necessity for tailored resilience strategies designed to address specific vulnerabilities known to exacerbate flood risk while simultaneously providing broader socioeconomic co-benefits for nearby civilian communities.